(untitled) (Journal of Laboratory Animal Science, 2024)
Due to a history of recurrences of Mouse Parvovirus (MPV) outbreaks, a novel procedural solution to environmentally screen previously contaminated rooms was explored. The authors wanted to evaluate a rapid, reliable means to test the environment without using animals by investigating the use of environmental swabs to detect residual MPV after rooms were depopulated and decontaminated. Polymerase Chain Reaction (PCR) was performed on environmental swabs to determine the presence of DNA that could be indicative of residual MPV in the affected rooms. The absence of MPV DNA demonstrated that the rooms were adequately decontaminated, and the likelihood of a re-infection was minimal after repopulation. The use of PCR to confirm the absence of environmental MPV has been an excellent method to determine the effectiveness of post outbreak decontamination.